Glenn Gould: The Performer in the Work. A Study in Performance Practice - Bazzana, Kevin (Oxford Clarendon, 1997)
This book is a detailed study of the great Canadian pianist, broadcaster, writer, and composer Glenn Gould (1932-82). While looking primarily on his performances, it also situates his work and thought more broadly within relevant musical, cultural, intellectual, and historical contexts. It incorporates most of the existing primary and secondary literature on Gould, as well as many ideas, interpretations, and perspectives that have never before been discussed. It also incorporates ideas from a wide range of literature, both musical and otherwise, and draws from unparalleled access to the Glenn Gould Papers in the National Library of Canada. The book offers a more comprehensive, balanced, and thoroughly researched portrait of Gould as pianist and interpreter than any previous volume in the Gould literature. Following an introduction that summarizes Gould's career and the posthumous interest in him, the book divides into two parts. Part 1, "Premises," focuses on the intellectual and aesthetic ideas that informed his performances, and draws on literature from many fields, including music history and aesthetics, cultural history, the history of performance practice, theatre, literary criticism, and music analysis. Part 2, "Practices," focuses in detail on Gould the pianist, illuminating important features of his style through prose description and critical analysis, and including graphic musical examples and plates.
Keywords: Gould, Glenn -- 1932-1982; 20th Century (1901-2000); Pianist; Performance